Indonesian Criminal Code, Living Law and Control in Law Enforcement in Indonesia - Selajar, Sophian Yahya; Martha, Aroma Elmina (Faculty of Law, Universitas Pattimura, 2023)
Introduction: The inclusion of the Living Law concept in the latest Criminal Code as a law that lives in society.Purposes of the Research: This paper analyzes the dialectic of legal certainty according to the principle of legality with living law as the principle of substantive justice in criminal law reform, from the perspective of law as a mechanism of social control and its influence on the dynamics of criminal law enforcement in Indonesia.Methods of the Research: This research uses a normative legal research model. Data collection is done through secondary data searches in the form of primary legal materials and secondary legal materials that are relevant to the object of the problem being studied. The approach used in the analysis is juridical-normative and then elaborated with a sociological approach through social science theories.Results of the Research: The results of the research on the accommodation of living law as a basic principle of criminal law have led to a dialectic between the principle of legal certainty and the principle of substantive justice. Living law is a form of law that is not codified like state law, but rather leads to awareness and cooperation among individuals in a community, so that the function applied is to control over community behavior, so that law enforcement mechanisms run naturally in order to maintain order and public morality.